Nutritional status and adherence to anti-tubercular treatment among tuberculosis patients in a community development block of Eastern India - Islam, Shahinoor; Das, Sulagna; Das, Dilip kumar (Indian journal of tuberculosis, 2024)
Undernutrition is a risk factor for developing tuberculosis (TB) and adherence to treatment leads to successful treatment outcomes. To assess the nutritional status and adherence to treatment among tuberculosis patients in Bhatar Community Development Block of Purba Bardhaman district, West Bengal, India. A cross sectional descriptive study was conducted among all the 82 tuberculosis patients registered between April to June, 2021, under NTEP in Bhatar tuberculosis unit (TU), who completed at least 1 month of therapy. Nutritional status was assessed based on BMI and adherence to treatment was evaluated by interviewing with a validated version of Morisky Medication Adherence Scale (MMAS-8-Item). Data was analysed using SPSS v23. Among the 82 subjects, 51 (62.2%) were found to be underweight and overall high level of adherence to treatment was found among 51 (62.2%) of study subjects. Subjects aged >45 years (AOR 3.686, 95% CI: 1.147–11.842) and having extra-pulmonary Tuberculosis (AOR 8.539, 95% CI: 1.305–55.871) were significantly associated as being adherent to treatment. Health education, awareness and more vigilant monitoring is still needed so that TB patients can be cured successfully. Special attention needs to be given on the nutritional status of the TB patients. •Poor nutritional status is an important co morbidity among TB patients.•Dietary supplementation is an important aspect for TB patients.•Poor adherance (only 62%) to treatment was another relevant finding of this study.